The mNutrition initiative content development stream - International Livestock Research Institute (International Livestock Research Institute, 2017)
This film gives a quick introduction to the mNutrition Initiative that is bringing safe, factual and targeted mobile advisory messages on health and agriculture to over 3 million people in 12 African and Asian countries.